2006
DOI: 10.1111/j.1472-8206.2006.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against α2‐adrenoceptors mediating relaxation in rat thoracic aortae: α2‐agonists relaxation depends on interaction with α1‐adrenoceptors

Abstract: In rat aorta, the presence of functional alpha(2)-adrenoceptors (alpha(2)-AR) was investigated in ring preparations preconstricted with alpha(1)-adrenergic and non- alpha(1)-adrenergic agonists. Particularly, the hypothetical interference of alpha(2)-AR agonists with alpha(1)-AR-mediated vasoconstriction was evaluated. Relaxant and contractile responses to alpha(2)-AR agonists were obtained. In endothelium-intact and endothelium-denuded aortic rings preconstricted with phenylephrine (1 x 10(-6) m), the imidazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Both inhibitors were added to the organ baths at the time when the medium was switch to CFM. In a second series of experiments, used to evaluate the mechanism underlying the PE (10 )6 mol ⁄ L)-induced contractile responses in the absence and presence of N G -nitro-L-arginine methyl ester (L-NAME; 10 )6 mol ⁄ L, 30 min), 12 superoxide dismutase (SOD; 100 U ⁄ mL, 15 min) 13 and indomethacin (10 )6 mol ⁄ L, 15 min, aortic segments were incubated with the inhibitors prior to the evaluation of PE-induced vasoconstrictor responses. 14…”
Section: Vasoconstrictor Responsesmentioning
confidence: 99%
“…Both inhibitors were added to the organ baths at the time when the medium was switch to CFM. In a second series of experiments, used to evaluate the mechanism underlying the PE (10 )6 mol ⁄ L)-induced contractile responses in the absence and presence of N G -nitro-L-arginine methyl ester (L-NAME; 10 )6 mol ⁄ L, 30 min), 12 superoxide dismutase (SOD; 100 U ⁄ mL, 15 min) 13 and indomethacin (10 )6 mol ⁄ L, 15 min, aortic segments were incubated with the inhibitors prior to the evaluation of PE-induced vasoconstrictor responses. 14…”
Section: Vasoconstrictor Responsesmentioning
confidence: 99%
“…Finally, l ‐NAME treatments did not significantly enhanced phenylephrine‐induced contractions in isolated aortic tissues, as could be expected as basal endothelial NO release may attenuate constrictor responses in rat aorta [29,30]. Nevertheless, the failure to obtain an increase in agonist‐induced constriction after endothelium removal in rat aorta has already been reported [31,32].…”
Section: Discussionmentioning
confidence: 64%
“…Besides being generally recognized as a potent central hypotensive agent, [27] clonidine is also known to induce vasodilation by acting directly on vascular adrenoceptors [25] . This peripheral response involves stimulation of endothelial α 2 ‐ARs as well as partial agonism towards α 1 ‐ARs of the vascular smooth muscle, and results in relaxation of endothelium‐intact strips previously contracted with phenylephrine (PE) [26, 28–30] . When testing if our analogues displayed a similar behaviour, we observed that exposure to UV light alone could induce relaxation of the vascular smooth muscle, substantially abolishing the contraction evoked by PE [31] .…”
Section: Resultsmentioning
confidence: 88%